Anomalies of Arch of Aorta and Its Branches - Computed Tomography Angiography Study. - Charitha, G.N.; Vasanthi, L.; Srinidhi, K. (Academia Anatomica International, 2019)
Introduction: The arch of aorta is a curved structure between the ascending aorta and the descending aorta.Three branches arise from the superior aspect of the arch- Brachiocephalic trunk, Left common carotid artery and Left subclavian artery. The aortic arch and its branches are well known for their anomalies which are important causes of cardio-vascular morbidity and mortality. The present study contribute for awareness and alertness regarding their incidence and prevalence for radiologists, cardiologists and endo-thoracic surgeons and to prevent complications during therapeutic procedures. Subjects and Methods: 500 CTA images were studied retrospectively from the patients who underwent chest and neck CTA for different reasons. Results: Out of 500 patients 474 (94.8%) patients had the classical branching pattern with left sided aorta. Six types of anomalies of the aortic arch and its branches were found in 26 (5.2%) patients. The most common anatomical variant was a common trunk for Brachiocephalic trunk and Left Common Carotid artery (bovine arch) found in 9 (1.8%) patients. In five (1%) patients, Left Vertebral Artery arises directly from the arch of aorta between left common carotid artery and left subclavian artery. Five (1%) patients had Right sided arch of aorta. Aberrant Right subclavian artery was found in four (0.8%) patients. Double arch in 2 (0.4%) cases and in one (0.2%) patient, we observed five branches arising directly from the arch, they are Right Common Carotid artery, Left Common Carotid artery, Left Vertebral artery, Left Subclavian artery and Aberrant Right Subclavian artery. Conclusion: With the ever increasing day to day advancements in complex endovascular interventions for the aorta and other great vessels of head and neck regions, early identification of aortic arch variant anatomy is of clinical significance to the radiologists and endovascular surgeons.